Thresholds in Caribbean coral reefs: implications for ecosystem‐based fishery management. Issue 2 (14th January 2015) - Karr, Kendra A.; Fujita, Rod; Halpern, Benjamin S.; Kappel, Carrie V.; Crowder, Larry; Selkoe, Kimberly A.; Alcolado, Pedro M.; Rader, Doug; Frid, C.
Summary Ecosystem‐based management of coral reef fisheries aims to sustainably deliver a diverse portfolio of ecosystem services. This goal can be undermined if the ecosystem shifts into a different state, with altered ecosystem functions and benefits to people. If levels of drivers that cause transitions between states are identified, management measures could be aimed at maintaining drivers below these levels to avoid ecosystem shifts. Analysing data from a large number of Caribbean coral reefs (N = 2001), suites of nonlinear thresholds were identified between metrics of coral reef processes and structure along a gradient of total fish biomass (a proxy for fishing pressure). Several metrics (macroalgal cover, invertivorous fishes and fish species richness) associated with coral‐dominated reefs exhibited thresholds at relatively high fish biomass levels (50–88% of unfished biomass). Other metrics (urchin biomass, ratio of macroalgal to coral cover, herbivorous fishes and coral cover) showed thresholds at lower fish biomass levels (28–37% of unfished biomass). Ratios of total fish biomass in fishing areas to closed areas (unfished biomass) in the Caribbean indicate that reefs may generally be at risk for change at ratios between 0·5 (coral dominated) and 0·3 (macroalgal dominated). Similar relationships were found for coral reefs in the Indian Ocean. While these results illustrate thresholds at the scale of the entire Caribbean, assessing local reefs is advisable because biomass levels vary within the region, and reef trajectories depend on past, present and future local conditions. Synthesis and applications. If the thresholds in this study are generalizable to scales relevant to management, it may be possible to produce sustainable yield while simultaneously maintaining coral‐dominated reefs by restricting fishing mortality to levels that result in biomass ratios near 0·5. Fishing down to biomass ratios near 0·3 may increase the risk of overfishing (resulting in lower long‐term yields) and transition to macroalgal‐dominated reefs. Thresholds offer a simple and powerful way for managers to operationalize precautionary ecosystem‐based fishery management by adaptively limiting fishing pressure in order to (i) maintain desirable coral reef conditions, (ii) establish a system‐specific target for generating pretty good yield and (iii) maintain sustainable multi‐species fishery yields.